(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Based on the analysis of the requirements of the profession to the personality of a specialist, the concept of professionalism is introduced. Professionalism is a set of personal characteristics of a person necessary for the successful performance of work. Pedagogical professionalism is a characteristic of a variety of interrelated components that reflect a specific educational system that meets the social order of society